(untitled) (TAMADDUN NURI JURNALI, 2024)
National independence made it possible to research Alisher Navoi’s art in a wide scope. The ideological-artistic world of Alisher Navoi’s “Khamsa”, tradition and creativity, interaction and artistry, plot and composition, system of images, genesis, typological aspects, along with issues of genre, weight, style, hermeneutic study of the work, studies of literary critic Aftondil Erkinov analyzed in the example.